TANGGAPAN MAHASISWA TERHADAP KEGIATAN SHADOWING DALAM MATA KULIAH CHOUDOKKAI - Widyaningtyas, Ika Hervina (Chi'e: Journal of Japanese Learning and Teaching, 2017)
The shadowing method is a method of repetition by listening to audio recordings. The shadowing method is a new method for Japanese Language Education Learning Program UNNES. The method was applied in 2011 mainly on learning Choukai. For students shadowing is unfamiliar methods used in learning, so that need for student responses about the shadowing activities. The problem in this research is how the responses of students to shadowing activities in the course Choudokkai. The purpose of this study was to determine the response of students about shadowing. The study was conducted by using the quantitative descriptive method by respondents as many as 25 students. The data collection technique using a combination of an open and closed questionnaire. Data were analyzed using frequency percentage formula. Based on the analysis that has been done, it can be concluded that as many as 64,8 % of the students understand the shadowing and shadowing activities can help students to learn Japanese on course Choudokkai.